Exploring The Interconnection Between Ethics and Religion: Its Contribution to Social Harmony - Makmur, Ahmad Diaz; Haris Kulle; Umar, Ratnah; Makmur, Afifah Idhelma (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This article examines the interconnection between ethics and religion and their contribution to social harmony. In the modern era, both Muslim and Western scholars recognize that humanity is facing a major moral crisis, in which scientific and technological progress has the potential to erode the essence of humanity. This study aims to analyze the concepts of ethics and religion, as well as their roles in building social harmony. This study offers a multidisciplinary and integrative approach to highlight how ethics and religion synergize in shaping the moral foundation of society. This study uses a descriptive and qualitative approach through a literature review, analyzing the concepts of ethics and religion and their contributions to social harmony. The findings reveal a strong connection between ethics and religion; both evaluate the goodness or badness of human actions. Ethics, rooted in common sense and conscience, serves as a rational guide, while religion, derived from divine revelation, provides a spiritual foundation that gives meaning and direction to life. Both function as individual rules and systems to maintain social balance, justice, and human dignity. Their collaboration fosters civilized individuals and forms the basis for sustainable civilization development.